RNA stability protein ILF3 mediates cytokine-induced angiogenesis - Vrakas, Christine N; Herman, Allison B; Ray, Mitali; Kelemen, Sheri E; Scalia, Rosario; Autieri, Michael V (The FASEB journal, 2019)
Interleukin enhancer-binding factor 3 (ILF3), an RNA-binding protein, is best known for its role in innate immunity by participation in cellular antiviral responses. A role for ILF3 in angiogenesis is unreported. ILF3 expression in CD31 capillaries of hypoxic cardiac tissue was detected by immunohistochemistry. Proangiogenic stimuli induce ILF3 mRNA and protein expression in cultured human coronary artery endothelial cells (hCAECs). Angiogenic indices, including proliferation, migration, and tube formation, are all significantly reduced in hCAECs when ILF3 is knocked down using small interfering RNA (siRNA), but are significantly increased when ILF3 is overexpressed using adenovirus. Protein and mRNA abundance of several angiogenic factors including CXCL1, VEGF, and IL-8 are decreased when ILF3 is knocked down by siRNA. These factors are increased when ILF3 is overexpressed by adenovirus. ILF3 is phosphorylated and translocates from the nucleus to the cytoplasm in response to angiogenic stimuli. Proangiogenic transcripts containing adenine and uridine-rich elements were bound to ILF3 through RNA immunoprecipitation. ILF3 stabilizes proangiogenic transcripts including VEGF, CXCL1, and IL-8 in hCAECs. Together these data suggest that in endothelial cells, the RNA stability protein, ILF3, plays a novel and central role in angiogenesis. Our working hypothesis is that ILF3 promotes angiogenesis through cytokine-inducible mRNA stabilization of proangiogenic transcripts.-Vrakas, C. N., Herman, A. B., Ray, M., Kelemen, S. E., Scalia, R., Autieri, M. V. RNA stability protein ILF3 mediates cytokine-induced angiogenesis.